THE CHALLENGES OF THE APPLICATION OF "MARKWARE" NOW IN ALGERIA - Nadia Ouchene (European Scientific Journal, ESJ, 2013)
The economy of the entire nation is continually influenced by the environment in general and particularly the political economic, marketing, management must serve at all times to enable the achievement of development goals. Again, it is imperative to force as an economic update to managerial vision for scoring the maximum possible developments and, as compared to wills change (given the globalization of markets and the revolution information in all its shapes), as compared to the drawbacks that firms are suffering from every day because of the competition, the existence of the informal sector and increased behavior of the consumer more unpredictable. Control competitiveness strengthened by managerial intercultural management leaves little choice for the company that aims at performance: it must ensure its ownership to its market as well as the overall supply. The effort of "adaptability" will cost the adoption of certain indisputable principles in marketing-management domain, which commit to further skills development... The "MarkWare" as proposed by Yves Le Golvan (marketing dictionary, 1988) implies that the company adopted eight key concepts of marketing management-all complementary, although some of them have more than one operational aspect Strategic these are the following fundamental concepts (as quoted by Yves Le Golvan): Market needs, vocation, positioning, marketing mix, differentiation, image, profitability and planning. The Algerian company (in this case public one) as far as it is concerned, witnesses fluctuating conditions due to imposed reforms without paved the way, as to make contradictory and generating crisis and deficit. Integrate "MarkWare" in a new context with a traditional economy requires that the undertaking concerned is seriously considering issues while undertaking a review of its management vision then a new approach involving as wholly adapted marketing. With regard to some investigations that we conducted with a sample of three Algerian public companies which already express a diagnosis denounce the consequences of instability and under management, we will try in what follows to study real issues in the applying of the "MarkWare" within them.